Changes in biochemical and functional parameters for men during exercise - Cesnaitiene Vida Janina; Karanauskiene Diana; Zaicenkoviene Kristina; Stasiule Loreta (Open Medicine, 2015)
Benefits of physical activity are undeniable. The aim of the present research was to determine the effects of physical activity and age on cholesterol and glucose levels in the blood, as well as changes in the functional parameters of the cardiovascular system, during stepwise increases in physical load for men employed in the same place, but with different levels of physical activity. The subjects were 95 military officers who were divided into groups according to the level of physical activity of their occupation, with veloergometry used as physical load. Cholesterol and glucose levels in the blood were taken as biochemical indices. The results showed that occupational physical activity had a positive effect on biochemical and cardiovascular functional parameters before, during, and after the physical load. Only the cardiovascular rate (systolic blood pressure) in older subjects was significantly higher than that of the younger persons; for all other parameters, age had no effect at all.